DISCRIMINATION, HEALTH MASTERY AND LIFE SATISFACTION AMONG BLACK AND WHITE OLDER WOMEN WITH BREAST CANCER. (11th November 2018) - Wallace, B; Baker, T
Abstract: Women diagnosed with breast cancer (BC) are often challenged when adjusting to their 'new normal' which involves balancing the desire to return to life prior to BC diagnosis with worry of disease recurrence. Identifying the internal and external psychosocial factors that impact positive adjustment - specifically, satisfaction with life - is critical to sustaining positive health trajectories. Therefore, this study investigated the underexplored roles of health mastery and perceived discrimination on life satisfaction (increasingly validated as a domain of adjustment) among older black and white women with BC in the third wave of the Midlife in the United States (MIDUS) study (n=95; mean [SD] age=68.81 [10.39] years; 96% white). When controlling for age, marital status, and education, higher internal health locus of control (IHLOC) was associated with greater life satisfaction (P<.05); moreover, when added to the model, a general measure of perceived daily discrimination was inversely related to life satisfaction (P<.05). Interestingly, while descriptive statistics revealed that experiences of gender discrimination (62.9%) were cited more often than race or age discrimination (11.4% and 45.7%, respectively), these factors were not statistically significant in the multivariate analyses. Findings reinforce the importance of IHLOC as an enhancing mechanism for life satisfaction post negative diagnosis and highlight the role of discrimination in disrupting life satisfaction. This research underscores the need to explore the impact of specific types of discrimination on the quality of life of BC patients – to advance the development of interventions addressing specific stressful life events on BC coping strategies.